Cooling Enhancement through Pulsation Flow in Microchannel Heat Sink - Mohd Saat, Fatimah Al Zahrah; Mohd Ghazali, Normah (2009)
Microchannel heat sink is now one of the most effective cooling techniques. As micropump works under pulsation regime and influenced by the possibility of heat transfer enhancement through pulsation, the goal has been to study the effect of pulsation to thermal behavior of microchannel heat sink. A computational model for studying pulsatile flow in microchannel had been developed using a commercial Computational Fluid Dynamics, (CFD) package FLUENT. The meshes generated had been tested for grid independency and the result numerically iterated by FLUENT had been validated and compared to various published data. The pulsating flow amplitudes were 50%, 70% and 90% of mean pressure and the flow regime is laminar. Pulsation tested was with frequencies in the range 500 Hz to 1.5 kHz. The results of pulsating flow simulations had been analysed and compared with the steady flow simulations. Pulsation had resulted in a lower wall temperature distribution, therefore enhanced cooling, compared to steady flow.